2023
DOI: 10.3389/fpls.2022.1051991
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient strategy to produce transgene-free gene edited plants in one generation using paraquat resistant 1 as a selection marker

Abstract: IntroductionDNA integration is a key factor limiting the marketing of CRISPR/Cas9-mediated gene edited crops. Several strategies have been established to obtain transgene-free gene edited plants; however, these strategies are usually time-consuming, technically difficult, providing low mutagenesis efficiency, and/or including a narrow host range.MethodTo overcome such issues, we established a paraquat resistant 1 (PAR1)-based positive screening (PARS) strategy, which achieved efficient screening of transgene-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Notably, loss-offunction mutations in the two close paralogs OsLAT1/OsPUT1 and OsLAT7/OsPUT2 did not convey resistance under these conditions. An independent study performed in parallel con rmed that loss-offunction mutations in AtPAR1 generated by CRIPSR/Cas9 can be used to identify edited lines (15). A similar approach that targeted the same three paralogs in rice as targeted here using a single construct showed that the triple oslat5/osput3/ospar1, oslat1/osput1, oslat7/osput2 mutants were also resistant to MV (30).…”
Section: Introductionmentioning
confidence: 75%
“…Notably, loss-offunction mutations in the two close paralogs OsLAT1/OsPUT1 and OsLAT7/OsPUT2 did not convey resistance under these conditions. An independent study performed in parallel con rmed that loss-offunction mutations in AtPAR1 generated by CRIPSR/Cas9 can be used to identify edited lines (15). A similar approach that targeted the same three paralogs in rice as targeted here using a single construct showed that the triple oslat5/osput3/ospar1, oslat1/osput1, oslat7/osput2 mutants were also resistant to MV (30).…”
Section: Introductionmentioning
confidence: 75%
“…While GMO concerns associated with genome editing could be resolved by segregating out the transgenic components through conventional crosses, a significant challenge remains when there is a desire to add muscat flavour to an existing elite grape for which the genetic makeup should otherwise be entirely maintained. There is extensive ongoing effort in developing transgene‐free editing systems, and one such system is to enrich transiently edited target genes using co‐editing genes such as ALS , MAR1 , and PAR1 as selection markers (Huang et al ., 2023; Kong et al ., 2023; Rinne et al ., 2021). Because most transgene‐free editing systems rely on transient editing, further optimization of various editing components for enhancing editing efficiencies continues to be a key area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we developed a recessive marker that is caused by loss of function of an endogenous rice gene, i.e., LAT5 / PUT3 / PAR1 , to confer resistance to the phytotoxin methylviologen (MV) as a method of selection. Note that, others used the LAT homolog PAR1 from Arabidopsis to establish a similar selection system [14]. Also in parallel, Lyu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1 μM MV blocked callus induction from WT mature embryos (Fig 5C), MV-based selection of lat5 / put3 / par1 calli directly after transformation or transfection is possible. In the case of Arabidopsis , PAR1 null alleles generated by CRISPR-Cas9 were shown to confer resistance to 1 µM and 10µM MV [14]. The authors stated that heritable transgene-free mutations at target loci were identified in the T1 generation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation